2023
DOI: 10.1042/ns20220034
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid signaling and epigenetics modifications in the neurobiology of stress-related disorders

Abstract: Stress exposure is associated with psychiatric conditions, such as depression, anxiety, and post-traumatic stress disorder (PTSD). It is also a vulnerability factor to developing or reinstating substance use disorder. Stress causes several changes in the neuro-immune-endocrine axis, potentially resulting in prolonged dysfunction and diseases. Changes in several transmitters, including serotonin, dopamine, glutamate, GABA, glucocorticoids, and cytokines, are associated with psychiatric disorders or behavioral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 269 publications
0
1
0
Order By: Relevance
“…Existing evidence indicates that stress-induced disruptions in the brain ECS signaling might be involved in the neurobiology of stress-related disorders such as PTSD and depression. Thus, the ECS is regarded as a potential target system for drug development in psychiatric disorders related to stress [49]. Previous studies have demonstrated that CB 1 receptor inhibition increases the symptoms of depression and anxiety [50,51], even in individuals without pre-existing conditions [52].…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence indicates that stress-induced disruptions in the brain ECS signaling might be involved in the neurobiology of stress-related disorders such as PTSD and depression. Thus, the ECS is regarded as a potential target system for drug development in psychiatric disorders related to stress [49]. Previous studies have demonstrated that CB 1 receptor inhibition increases the symptoms of depression and anxiety [50,51], even in individuals without pre-existing conditions [52].…”
Section: Discussionmentioning
confidence: 99%